Two dryinid species new for Fennoscandia with a re-evaluation of the generic division of N. European Gonatopodinae (Hymenoptera, Dryinidae) - Vikberg, Veli; Koponen, Martti (Entomologica Fennica, 2001)
Bocchus vernieri Olmi, 1995 was found in Ta: Tammela, southern Finland, as the first species of the subfamily Bocchinae for Fennoscandia; it is a new species for N. Europe. Gonatopus horvathi Kieffer, 1906 is added to the fauna of Finland; it is also a new species for Northern Europe. The two species are further described on the basis of the new material. The generic position of North European species of Gonatopodinae is re-evaluated, and it is concluded that a single genus, Gonatopus Ljungh, should be recognized, to include two subgenera, Dicondylus Haliday (Haplogonatopus R. C. L. Perkins, syn. nov.) and Gonatopus s. str. In the Appendix Bocchus italicus Olmi, 1984 is reported from Corfu as new to the fauna of Greece.